PSIKOLINGUISTIK DALAM METODOLOGI PEMBELAJARAN BAHASA ARAB DI ERA POSTMETODE - Yusuf, Muhammad (STIQ Amuntai, 2019)
This paper aims to present the theory of psycholinguistics as a basis for developing the methodology of learning Arabic in the post methods era. This study encouraged by the emergence of new trends related to the Arabic learning methodology. In this trend, the methodology was formulated based on academic readings from various perspectives, one of which is psycholinguistics. This paper relies on bibliographic sources in the form of books and articles (literature studies) that are in scientific journals related to the subject matter. Reading the data of thought by academics using a critically constructive approach and meaning of the substance using content analysis. Based on the studies that have been conducted, in the context of post methods, the psycholinguistic theory was seen as a building that used as a foundation in developing learning models. Where in this era is marked by the reduction of the role of methods in language learning? The learning model that was born based on this assumption is active, cooperative learning, and (pakem) learning. Furthermore, in applying this model, the teacher is required to play an optimal role. The integral form, the teacher is required to have personal competence, social competence, and professional competence. This study has a significant urgency considering the post-method trend is a formula that results from the academic reading of a psycholinguistic-based teacher to utilize learning activities in the classroom.